The Use of Montmorillonite (MMT) in Food Nanocomposites: Methods of Incorporation, Characterization of MMT/Polymer Nanocomposites and Main Consequences in the Properties - Vilarinho, Fernanda; Vaz, Malia Fátima; Silva, Ana S. (Recent Patents on Food, Nutrition & Agriculture, 2020)
Background: The clay Montmorillonite (MMT) is among the nanofillers more frequently used in food packaging. The uniform dispersion of nanoparticles in polymers confers considerable improvement of mechanical, thermal, optical, and/or barrier properties in polymer/clay nanocomposites. Objective: The aim is to ascertain the state of the art of the use of MMT for packaging purposes, with special emphasis on food applications. Methods: A literature review was carried out through recent papers and patents that focused on the incorporation of MMT in polymers. Results: This review emphasizes the interaction of MMT with polymers and their levels of incorporation in the nanocomposites. This work also highlights the analytical methodologies used for the characterization of the polymer/clay nanocomposites and the main consequences of the fillers in the properties of nanocomposites. Challenges remain about increasing the compatibility between clays and biopolymers to promote their utilization in food packaging. New strategies for immobilization of oxides, enzymes, essential oils, and other bioactive compounds are needed. Conclusion: MMT-based composite materials are promising to be used in intelligent and active packaging.
Keywords: nanocomposites